Four Levels of Teachers: Insights into Classroom Leadership Perspectives - Asbari, Masduki (IJOSMAS, 2024)
This research employs a descriptive qualitative approach, gathering data through participatory observation, interviews, and document analysis. The study includes a sample of educators teaching across various educational levels, from primary to secondary. The findings delineate four levels of teacher performance within the classroom leadership context, emphasizing interpersonal relationships with students, colleagues, and the broader learning community. Beginning with Level R1 (Right) teachers, who adhere strictly to decrees or assignment letters. Level R2 (Relationship) teachers are characterized by strong emotional bonds with students, colleagues, and other members of the learning community. Level R3 (Respect) teachers command respect from learners, colleagues, and other members of the learning community due to their exemplary behavior. Level R4 (Result) teachers are those who effectively enhance the dignity of their students based on their individual talents. The journey of advancing teacher leadership from R1 to R4 encompasses elements such as caring, modeling, and coaching. Moreover, the spiritual energy essential for teachers to continually elevate their levels is emphasized. By underscoring the significance of strong interpersonal relationships in shaping teacher effectiveness and its broader implications for enhancing the overall quality of education.